2017
DOI: 10.1002/nag.2745
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soil‐structural interface behavior using three‐dimensional DEM simulations

Abstract: The shear behavior at the interface between the soil and a structure is investigated at the macroscale and particle-scale levels using a 3-dimensional discrete element method (DEM). The macroscopic mechanical properties and microscopic quantities affected by the normalized interface roughness and the loading parameters are analyzed. The macro-response shows that the shear strength of the interface increases as the normalized roughness of the interface increases, and stress softening and dilatancy of the soil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 53 publications
0
31
1
Order By: Relevance
“…In [55], the boundary conditions along the horizontal rigid wall suggested inclusion of two ratios connected to the normalized wall roughness (a ratio of the micro-polar rotation multiplied by the mean grain diameter and the horizontal displacement and a ratio of the horizontal shear stress multiplied by the mean grain diameter and the horizontal couple stress). To better understand microscopic phenomena during wall friction, DEM calculations were also carried out [4,5,12,14,15,22,24,25,62,63,70,77,78]. There exist many numerical studies of wall friction using DEM under 2D conditions (e.g.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In [55], the boundary conditions along the horizontal rigid wall suggested inclusion of two ratios connected to the normalized wall roughness (a ratio of the micro-polar rotation multiplied by the mean grain diameter and the horizontal displacement and a ratio of the horizontal shear stress multiplied by the mean grain diameter and the horizontal couple stress). To better understand microscopic phenomena during wall friction, DEM calculations were also carried out [4,5,12,14,15,22,24,25,62,63,70,77,78]. There exist many numerical studies of wall friction using DEM under 2D conditions (e.g.…”
Section: Literature Overviewmentioning
confidence: 99%
“…There exist many numerical studies of wall friction using DEM under 2D conditions (e.g. [14,15,22,62,63,77,78]) and only a few under 3D conditions [4,5,12,24,25,70]. To facilitate the interpretation of macroscale responses, microscale metrics such as contact normal force distribution, contact networks, mobilization of friction, and particle rotation were calculated to elucidate the wall friction mechanism.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Note that negative skin friction develops at the column shaft, increasing the stress and compression on the column and reducing the stress and compression in the surrounding soil. The deformation shape of the latter is hard to determine and is influenced by certain factors, such as soil structure interactions (Zhou and Yin, 2008;Yin and Zhou, 2009;Su et al, 2010;Zhou et al, 2011;Hokmabadi et al, 2014;Suleiman et al, 2016;Meguid et al, 2017;Yu and Bathurst, 2017;Zhu et al, 2017;Jing et al, 2018;Wang et al, 2018b) and constitutive models adopted for subsoil (Yin et al, , 2010a(Yin et al, , 2010b(Yin et al, , 2011a(Yin et al, , 2011bSexton et al, 2016;Yin et al, 2017). Alamgir et al (1996) innovatively proposed a deformed shape function to investigate the performance of a column-reinforced foundation, which is applied here for this purpose.…”
Section: Behavior Of Column Embedded Subsoilmentioning
confidence: 99%
“…Wang and Jiang, via a comparison between interface and direct shear test methods, showed that the SSI's shear strength is essentially the mobilized soil strength of the rough surface. In a later paper, Jing et al reported that for an SSI rougher than a certain value, the shear strength can be approximate to the strength of the soil itself. In fact, a soil phase with a highly nonlinear constitutive behavior gives rise to a complex mechanical response of SSI to the shear load.…”
Section: Introductionmentioning
confidence: 99%